Receiver system optimization for digital video broadcast (DVB) - Teo, Guan Hing. (2008)
This dissertation attempts to study the fundamentals of the function of the various Digital Television Broadcast protocols, with special focus on the widely adopted Digital Video Broadcast -Terrestrial (DVB-T), a European standard. DVB-T has been developed to provide robust and high capacity data streaming of video signal. It based on Coded Orthogonal Frequency Division Multiplexing (COFDM), strong encoding scheme for Forward Error Correction and special timing slots for signal synchronization, in the multi-path urban environment.